2018
DOI: 10.1016/j.celrep.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Improving Cell Survival in Injected Embryos Allows Primed Pluripotent Stem Cells to Generate Chimeric Cynomolgus Monkeys

Abstract: Highlights d Optimizing culture media for injected morulae inhibits primed PSC apoptosis in embryos d Improved survival of pPSCs injected into embryos generates chimeric monkeys d Embryonic microenvironment reprograms injected PSCs to embryonic-like cells d Reprogramming level and chimerism are related to the cell state of injected PSCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Although it is ambiguous whether the STB-like syncytia are derived through the progenitor state corresponding to embryonic CTBs, these results indicate that human pESCs possess the competence to give rise to not only STBs in primitive syncytium of the implantation embryo but also an in vitro counterpart of villous CTBs in the firsttrimester placenta. In a previous report, monkey pESCs were shown to contribute to the placental tissue when injected into the morula stage of the monkey embryo, supporting our results (Kang et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Although it is ambiguous whether the STB-like syncytia are derived through the progenitor state corresponding to embryonic CTBs, these results indicate that human pESCs possess the competence to give rise to not only STBs in primitive syncytium of the implantation embryo but also an in vitro counterpart of villous CTBs in the firsttrimester placenta. In a previous report, monkey pESCs were shown to contribute to the placental tissue when injected into the morula stage of the monkey embryo, supporting our results (Kang et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Primate ESCs exist in a different phase of pluripotency than rodent ESCs, as they are primed rather than naïve (Brons et al, 2007;Nichols and Smith, 2009; Boroviak et al, 2014). The ratio of cmESCs in allogenic chimeras is only 0.1%-4.5% (Chen et al, 2015;Kang et al, 2018), which is significantly lower than with rodents. However, in previous reports, naïve hPSCs have lacked the competency to integrate into the mouse embryo (Gafni et al, 2013;Theunissen et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…In our domestication system, the cell and embryo culture media were mixed in an optimal ratio, increasing the anti-apoptotic ability of cmESCs and improving the development of pig embryos, and allowing the successful generation of chimeric animals. Improvement of the culture conditions also played an important role in a previous homozygous chimera study (Kang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that inhibiting apoptosis either by the addition of the Rock inhibitor Y27632 (Kang et al, 2018), or by overexpression of the anti-apoptotic genes BCL2 (Masaki et al, 2016) or BMI1 (Huang et al, 2018) enables primed PSCs to colonize host embryos. Therefore, in a final series of microinjections, we asked whether inhibition of apoptosis could improve the engraftment of naïve PSCs into the host embryo.…”
Section: Premature Differentiation Of Rhesus Naïve Pscs After Injectimentioning
confidence: 99%